2016
DOI: 10.1002/fsn3.452
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid profile and protein quality in tuber and leaf of Coccnia abyssinica (Lam.) (Cogn.) accessions of Ethiopia

Abstract: The protein content and amino acid profile of Anchote (Coccinia abyssinica) leaves and tubers were determined from ten different accessions taken from Debre Zeit Agricultural Research Center, Ethiopia. Crude protein content was determined by Kjeldahl method and amino acid profile was analyzed using performic acid oxidation and acid hydrolysis by ninhydrin‐derivatized analysis with amino acid analyzer. Crude protein content of Anchote tuber ranged from 10.70% ± 0.26% to 13.72% ± 0.10%, whereas the crude protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…P-PER values of W. cibaria FB-069 and W. viridescens FB-077 salted squid were 1.3 and 1.6, respectively. They are close to the P-PER value of 1.21 for cowpea and 1.22 for tuber anchote (Salunkhe and Kadam 1989;Ayalew et al 2017). However, they are lower than the P-PER value of 2.5 for reference casein from cow's milk protein (WHO 1985).…”
Section: Nutritional Analysissupporting
confidence: 82%
“…P-PER values of W. cibaria FB-069 and W. viridescens FB-077 salted squid were 1.3 and 1.6, respectively. They are close to the P-PER value of 1.21 for cowpea and 1.22 for tuber anchote (Salunkhe and Kadam 1989;Ayalew et al 2017). However, they are lower than the P-PER value of 2.5 for reference casein from cow's milk protein (WHO 1985).…”
Section: Nutritional Analysissupporting
confidence: 82%
“…The similar determination of free amino acids in the methanol extracts of Acacia and Eucalyptus leaves by GC-MS method with TBDMS derivatives [46] demonstrated that only a few free amino acids were identified including proline, methionine, phenylalanine, cysteine, and lysine. By the other investigation [47], arginine, leucine and glutamic acid in tubers and leaves of Coccinia abyssinica had the highest content among all amino acids. Besides, the average amino acid content was higher in the leaves compared to the tubers, that is corresponding to the current investigation of Iridaceae plant extracts.…”
Section: Discussionmentioning
confidence: 74%
“…Limited information is available on the amino acid composition and protein quality of the anchote tuber. Only recently (in December 2016), Ayalew et al [ 18 ] provided some details on the amino acid profile of anchote tuber protein. The essential amino acids for the tuber varied from 32.98–41.63% with an average of 37.22% [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only recently (in December 2016), Ayalew et al [ 18 ] provided some details on the amino acid profile of anchote tuber protein. The essential amino acids for the tuber varied from 32.98–41.63% with an average of 37.22% [ 18 ]. The result from this study further added that arginine was the highest and methionine was of the lowest concentration with 6.5–9.5 and 0.3–0.4 g/100 g protein, respectively [ 18 ].…”
Section: Resultsmentioning
confidence: 99%